Comprehensive clinical sitting balance measures for individuals following stroke: a systematic review on the methodological quality - Birnbaum, M.; Hill, Keith; Kinsella, R.; Black, S.; Clark, R.; Brock, K. (Informa Healthcare, 2018)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. Purpose: The aim of this systematic review was to examine the psychometric properties of published clinical sitting measurement scales containing dynamic tasks in individuals following stroke. Method: Databases, including Cumulative Index of Nursing and Allied Health Literature (CINAHL), MEDLINE, EMBASE, Cochrane, PubMed and Allied and Complementary Medicine Database (AMED) were searched from inception to December 2015. The search strategy included terms relating to sitting, balance and postural control. Two reviewers independently selected and extracted data from the identified articles and assessed the methodological quality of the papers using the COnsensus-based Standards for selection of health status Measurement INstruments (COSMIN) checklist. Results: Fourteen clinical sitting measurement scales (39 papers) containing dynamic tasks met the inclusion criteria and various measurement properties were evaluated. The methodological quality of the majority of the included studies was rated as poor to fair using the COSMIN checklist, with common limitations including small sample size and inappropriate use of statistical methods. Conclusions: This review was unable to identify measures with sufficient psychometric properties to enable recommendation as preferred tools. However, measures were identified that warrant further specific psychometric investigations to fulfil requirements for a high quality measure.Implications for Rehabilitation Fourteen clinical sitting balance scales containing dynamic tasks are available to measure sitting balance with individuals following stroke. No single scale has sufficient psychometric properties to enable recommendation as a preferred tool for measuring sitting balance with stroke survivors. Use of a balance scale or dedicated sitting balance measure containing static and dynamic sitting items should be utilised to monitor progress for individuals following stroke with more severe deficits.